Millimeter‐wave phase shifter based on waveguide‐mounted RF‐MEMS. Issue 3 (28th January 2013) - Psychogiou, Dimitra; Li, Yunjia; Hesselbarth, Jan; Kühne, Stephane; Peroulis, Dimitrios; Hierold, Christofer; Hafner, Christian
Abstract A continuously variable transmission type W‐band phase shifter based on a single pole bandpass filter tuned by MEMS actuated fingers is reported. Tuning is achieved by means of two half‐wavelength long conductive fingers that synchronously rotate upwards in an antiparallel fashion. The fingers deflection results in a distributed variable shunt capacitance which in turn leads to a variable analog phase shift. For an applied DC bias voltage between 0 and 26 V, the transmission phase can be continuously varied up to 46.4° at a frequency of 106 GHz with an insertion loss of less than 3.4 dB. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 54:465–468, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27390